Transforming Sourcing and Supply Chain Management: The Evolution of AI Agents in Modern Procurement - Parameswara Rao Tatini (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of artificial intelligence and machine learning technologies on procurement and supply chain management practices. The article shows how AI agents are revolutionizing traditional procurement processes through advanced data analytics, automated decision-making, and predictive capabilities. By analyzing implementations across manufacturing, retail, and technology sectors, the research demonstrates how AI-powered solutions are addressing longstanding challenges in supplier selection, demand forecasting, contract management, and risk mitigation. The article explores the evolution from manual to AI-driven processes, highlighting improvements in operational efficiency, cost optimization, and strategic decision-making. Furthermore, it examines the integration of emerging technologies like blockchain and smart contracts in procurement systems, while considering critical implementation challenges such as data privacy, legacy system integration, and skill gaps. The article provides comprehensive insights into how organizations are leveraging AI to transform procurement from a purely operational function to a strategic driver of business value, while also addressing the growing importance of sustainable and ethical procurement practices in the modern business landscape.